Climate Change and Migration: The Case of Africa - Bruno Conte (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper estimates the impacts of climate change in sub-Saharan Africa (SSA) on migration and other economic outcomes. I develop a quantitative spatial model that captures the role of trade networks, migration barriers, and agricultural yields on the geography of the economy. I combine the model with forecasts of future crop yields to find that climate change, by the end of the century, reduces SSA real GDP per capita by 1.8 percent and displaces 4 million individuals. Migration barriers in SSA are very stringent: if absent, climate-induced migration exceeds 100 million individuals. Still, migration and trade are powerful adaptation mechanisms. Reducing migration barriers to the European Union (EU) standards eliminates the aggregate economic losses of climate change in SSA, but at the cost of more climate migration and higher regional inequality. Also reducing trade frictions to the EU levels attenuates this cost and makes SSA better off on aggregate and distributional terms.
Keywords: O15; Q54; R12; 330; climate change; migration; economic geography